(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
The Complex roots of a Quadratic equation has been investigated analytically while we deal with numbers purely in real domain .The imaginary or complex roots give a deep insight of this roots of quadratic equation .Here we are trying to analyze the roots of quadratic equation graphically. Some examples are examined in two dimensional and three dimensional graphacially.